Uma proposta de sequência didática funcionalista - Duarte, Milcinele da Conceição (2015)
This thesis aims at proposing a functionalist didactic sequence for High School (FDS). The linguistic analysis perspective bears as its basic conception the notion of language as an instrument of verbal interaction, which is equivalent to social interaction. The proposal is based on the metafunctions performed by language in its use, on the recognition of the text as a basic unit of study and on the consideration of the discursive textual genres as the sphere of interactive activity. Essay, as a genre, is studied as an interaction event and as an expression of content. Therefore, the discursive textual genres as a teaching tool are included and this enables the study of grammar considering language in use, not isolated from the language experience. This study considers the syntactic, semantic and pragmatic relations activated in the verbal interaction process. The functionalist theoretical foundations are from Halliday (1973), Dik (1989) Neves (1997, 2010, 2011, 2013), Rauber (2005) and Antunes (2003, 2009), among others. The theoretical-methodological basis which ranges from PCNs (1998) and PCNEM (2000) is updated upon authors such as Franchi (2006), Pauliukonis (2011), Casseb-Galvão (2011) as well as Kuhn and Flores (2008). The didactic sequence notions used in the proposal come from Zabala (1998), Dolz, Noverraz and Schneuwly (2004). The didactic sequence proposed in this thesis, far from being a finished and ready application model, is a guiding and reflection tool, an example of didactic transposition of the linguistic theory contributions for teaching as well as an aid for other language teaching didactic principles. Moreover, we understand that teaching should range from a social and verbal interactive activity. This means language is regarded as a functioning system linked, therefore, to the concrete and diverse circumstances of its updating process. Thus, the activities proposed in FDS include following conceptual, procedural and attitudinal contents, enabling the student to act reflectively, meet challenges, discuss issues and understand the functionality of linguistic choices promoted by the texts, as proposed by Neves (2010). The pilot experience of application of didactic sequence occurred in seven public schools of Santarém, Pará in the fourth bimester of the 2014 school year. We have been attentive to the receptivity of the subjects of teaching and learning and to the external factors which interfered with the application of this proposal. The FDS proved to be relevant and it confirmed the hypothesis that as long as there is a physical infrastructure and suitable policy, this educational tool can be useful and inspiring for the Portuguese language teaching in Elementary, Middle and High school, particularly in High school.